Ultrafast isomerization dynamics of bisazobenzenes - Slavov, Chavdar; Yang, Chong; Dreuw, Andreas (International Conference on Ultrafast Phenomena 2016, Santa Fe, New Mexico United States, 17-22 July 2016, 2016)
Ultrafast transient absorption was used to study the isomerization dynamics of bisazobenzenes - a model system for multiphotochromic constructs. The dynamics and the quantum efficiency is strongly dependent on the connectivity pattern between the individual units.
From the session Dynamics of Molecular Systems (UTh3B)
Gesehen am 06.12.2017
Keywords: Konferenzschrift